Public-private partnership (PPP) learning resources (Asian Development Bank, 2007)
The compilation of presentations and reading materials is about the creation of value for money and utilization of private capital investment by evaluating the private sector's comparative advantage and entrepreneurial capacity with emphasis on the risk of spending the private capital investment in the delivery of public service.